2010
DOI: 10.1111/j.1740-0929.2009.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Collagen content and architecture of the pectoralis muscle in male chicks and broilers reared under various nutritional conditions

Abstract: Varying chicken growth rates were induced with different nutritional regimes, and the collagen content and architecture of M. pectoralis (PT) were compared among 21-day-old chicks and broilers at 80 or 95 days of age. The percentage of muscle weight to live weight was higher in rapid growing chicks (8.4%) than slow growing chicks (6.3%). The 80-day-old broilers engaged in compensatory growth after the early slow growth period producing PT muscle at 11% of live weight. The 80- and 95-day-old chicks with restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The muscle grew through rapid accumulation of protein for muscle fibre growth and had a relatively slower deposition of collagen around muscle fibres (Swatland, 1990;Shiba et al, 2006). Das et al (2010) found that the collagen concentration was higher in the late-growth restricted broilers than the compensatory growth broilers. The perimysium collagen fibres seemed to have retarded development in the compensatory growth broilers.…”
Section: Relationship Between Muscle Fibre Characteristics and Carcasmentioning
confidence: 87%
See 1 more Smart Citation
“…The muscle grew through rapid accumulation of protein for muscle fibre growth and had a relatively slower deposition of collagen around muscle fibres (Swatland, 1990;Shiba et al, 2006). Das et al (2010) found that the collagen concentration was higher in the late-growth restricted broilers than the compensatory growth broilers. The perimysium collagen fibres seemed to have retarded development in the compensatory growth broilers.…”
Section: Relationship Between Muscle Fibre Characteristics and Carcasmentioning
confidence: 87%
“…The perimysium collagen fibres seemed to have retarded development in the compensatory growth broilers. The thickness of collagen fibres increased with aging (Fang et al, 1999;ochowska et al, 2005;Das et al, 2010). The increasing of the crosslinking demonstrates a positive correlation with insoluble collagen (Wojtysiak, 2013).…”
Section: Relationship Between Muscle Fibre Characteristics and Carcasmentioning
confidence: 99%
“…Results obtained for Landrace pigs (Fang et al, 1999;Nishimura et al, 2009) showed an average perimysium width (perimysium surrounding secondary bundles) of 24 μm for 6 month pigs. In chicken, Das et al (2010) showed a perimysium width for broilers (8 weeks) ranging from 30 μm (thick perimysium) to 10 μm (thin perimysium). An et al (2010) determined a perimysium width for chicks (6 to 18 weeks) ranging from 14 μm to 39 μm.…”
Section: Discussionmentioning
confidence: 99%
“…Except Sifre-Maunier, Taylor, Berge, Culioli, and Bonny (2006) and Del Moral, O'Valle, Masseroli, and Del Moral (2007), authors have rarely described their method accurately. Image analysis has been used to study the structural characteristics of perimysium thickness Brooks & Savell, 2004;Das et al, 2010;Fang, Nishimura, & Takahashi, 1999;Lachowicz, Zochowska, & Sobczak, 2004;Nishimura, Fang, Wakamatsu, & Takahashi, 2009;Sifre-Maunier et al, 2006;Torrescano et al, 2001) or muscle fibre bundles, but few authors have been interested in endomysium Lachowicz et al, 2004;Torrescano et al, 2001). This may be explained by the fact that the major part of the IMCT is perimysium (Light & Champion, 1984;Light, Champion, Voyle, & Bailey, 1985).…”
Section: Introductionmentioning
confidence: 97%
“…It is suggested that collagens, the major protein constituent of the perimysial and endomysial connective tissues [ 4 , 20 ], are the major determinant of muscle texture, primarily influencing the muscle quality, rather than the muscle quantity. Skeletal muscle contains several types of collagens, such as types I, III, IV, V and VI collagens [ 18 ], but the collagen constituting the perimysium and endomysium of skeletal muscle is mainly type I collagen [ 1 , 3 , 20 ].…”
mentioning
confidence: 99%